2018
DOI: 10.1159/000485894
|View full text |Cite
|
Sign up to set email alerts
|

Boiling and Pressure Cooking Impact on IgE Reactivity of Soybean Allergens

Abstract: Background: Soybean is one of the 8 foods that causes the most significant rate of food allergies in the USA and Europe. Thermal processing may impact on the allergenic potential of certain foods. We aimed to investigate modifications of the IgE-binding properties of soybean proteins due to processing methods that have been previously found to impact on the allergenicity of legumes such as peanut. Methods: Soybean seeds were subjected to different thermal processing treatments. To evaluate their impact on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Soybean products are a major source of food allergies. Cabanillas et al [69] investigated the impact of thermal and pressure processing of soybeans on specific IgE binding capacity in a small cohort of sensitized individuals. They found that boiling for 60 min led to reduced IgE binding ex vivo.…”
Section: Food Allergymentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean products are a major source of food allergies. Cabanillas et al [69] investigated the impact of thermal and pressure processing of soybeans on specific IgE binding capacity in a small cohort of sensitized individuals. They found that boiling for 60 min led to reduced IgE binding ex vivo.…”
Section: Food Allergymentioning
confidence: 99%
“…They found that boiling for 60 min led to reduced IgE binding ex vivo. Pretreatment that combined both heat and pressure seemed to be more effective, exhibiting an even more pronounced reduction in IgE binding ex vivo, as well as reduced skin prick testing wheal size in patients ex vivo [69]. …”
Section: Food Allergymentioning
confidence: 99%
“…Measures as fermentation with microorganisms boiling and pressure cooking genetical modification and other measures can degradate major allergens and achieve a reduction of soybean hypersensitivity. Removal of soybean oil in intralipid for total parenteral nutrition have been also proposed [41][42][43][44][45].…”
Section: Recent Advances In the Control Of Allergic Reaction To Soybeanmentioning
confidence: 99%
“…Food processing aims at providing a safe and nutritious diet to promote the health of the consumers. In this context, soybean can be processed in several ways before human consumption such as cooking, fermenting, grinding among others (Cabanillas et al, 2018). Thermal processing, in particular, can lead to different structural/sequential modifications of the proteins, such as aggregation phenomena and formation of new molecular bonds, rearrangement of the disulfide bonds, breakdown of peptide bonds and chemical modification of amino acids within the protein structure (Ashaolu, 2020;Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%